Dynamics of Collaboration in Poverty Alleviation in Bone Regency - Akbar, Andi; Usman, Jaelan; Malik, Ihyani (Borong Newinera Publisher, 2024)
This research is to analyze dynamics of collaboration in poverty alleviation in Bone Regency. The method used is descriptive qualitative with a phenomenological approach. Results of interviews as primary data and secondary data through documents and literature related to the topic. The results of the study show that in principle movement, motivation and ability to act together goes through coordination meetings which are held at least 4 times a year or quarterly. Collaborative actions through community empowerment, establishment of licensing processes, human resources and a new management system are also ongoing with the existence of the District Coordination Team which directly monitors the process of distributing aid in the field. Another thing is intended to avoid the occurrence of multiple KPM recipients, by using the NIK identity through the SIKS-NG application to make it easier to check beneficiary data. The main supporting factor is the synergy of stakeholders to overcome poverty. However, the obstacles are the people's mindset which is still difficult to change and the network is less stable in some areas.